A Modified Conjugacy Condition and Related Nonlinear Conjugate Gradient Method. (18th March 2014) - Yao, Shengwei; Lu, Xiwen; Qin, Bin
Abstract : The conjugate gradient (CG) method has played a special role in solving large-scale nonlinear optimization problems due to the simplicity of their very low memory requirements. In this paper, we propose a new conjugacy condition which is similar to Dai-Liao (2001). Based on this condition, the related nonlinear conjugate gradient method is given. With some mild conditions, the given method is globally convergent under the strong Wolfe-Powell line search for general functions. The numerical experiments show that the proposed method is very robust and efficient.